PENGARUH PERBANDINGAN RUMPUT LAUT SEGAR Ulva lactuca DENGAN LARUTAN ASAM CUKA TERHADAP KARAKTERISTIK BIOPLASTIK ALGINAT - Pramananta, I Ketut; Harsojuwono, Bambang Admadi; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 3 (2019): SeptemberDO - 10.24843/JRMA.2019.v07.i03.p12, 2019)
This study aims to determine the effect of the comparison of Ulva lactuca and vinegar acid on the characteristics of bioplastic alginate and determine the comparison of seaweed with the right vinegar solution so as to produce the best bioplastic alginate characteristics. This study uses a completely randomized design with a comparison treatment of Ulva lactuca seaweed with dissolved sam vinegar. The experiment was carried out with a ratio of 0.5: 2.5, 1.0: 2.0, 1.5: 1.5, 2.0: 1.0, 2.5: 0.5 with the treatment repeated 4 times so that 20 experimental units were obtained. Variables observed were tensile strength, percent extension, Young Modulus, thickness, biodegradation. The results of this study showed that vinegar acid solution had a significant effect on tensile strength, percent extension, Young Modulus, period of biodegradation and thickness of plastic. Comparison of seaweed and vinegar (2.5: 0.5). produce the best bioplastic alginate with characteristics: the percentage of biodegradation loss value 0,49% - 0,51%, increasing thickness period of 218,25 µm, tensile strength 1,86 MPa, Young Modulus 14,55 MPa and bioplastic extension 34,91%. Keyword : bioplastic, Alginate, Ulva lactuca and vinegar acid solution